Physical activity patterns in healthy and cognitively impaired older Chileans using wireless‐enabled wearable technology devices: Prevention (nonpharmacological) / Exercise. (7th December 2020) - Rogers, Nicole; Lazcano, Joaquin; Herrera, Sebastian; More, Jamileth; SanMartín, Carol D; Bennett, Magdalena; Romero, Cesar; Grinspun, Noemí; Valdés, Jose L; Behrens, María Isabel
Abstract: Background: Increasing physical activity (PA) benefits cognition in older adults, both healthy and cognitively impaired. However, there is a lack of knowledge in the baseline amount and type of PA performed by this age group, especially in underrepresented populations. Furthermore, previous studies with other populations have almost exclusively focused on self‐reported and caregivers' questionnaires, which are considered limited tools for assessing PA and exercise. Method: We recruited 77 people between the ages of 60 and 91 (average: 72.7 years) from different neighborhoods is Santiago de Chile, both cognitively healthy and with varying degrees of cognitive impairment. They underwent gait and neuropsychological evaluations and a thorough interview and neurological exam. Their PA was registered for a month with the use of a smart wristband activity monitor (Fitbit Alta HR). Daily steps, time spent inactive (sedentary activity, SA), in light physical activity (LPA), and moderate to vigorous physical activity (MVPA) were determined with the help of the algorithms provided by Fitbit. Result: Healthy participants (HP)(n=53), amnestic mild cognitive impaired (aMCI) patients (n=14), and mild Alzheimer disease (AD) patients (n=10) averaged 6700 steps a day (HP=7015, aMCI=6700, AD=4910). There were no statistically significant differences in mean daily steps between the groups, nor in time they spent in sedentary activity, LPA, and MVPA. There were no significant differences between sexes for these variables. HP, aMCI, and AD patients registered an average of 140%, 220% and 250% more time in SA than what they had previously self‐reported, respectively; interestingly, healthy participants self‐reported higher time spent in SA than the cognitively impaired but average higher means of daily steps, and more time in LPA and MVPA. There was a significant inverse correlation between age and mean daily steps, and with LPA. Conclusion: The use of wireless wearable‐technology offers a unique opportunity to study to role of PA patterns in other non‐transmissible diseases in healthy and cognitively impaired older individuals. More focus should be put in the prevention of sedentarism and the promotion of PA and exercise since it offers an approachable and measurable way of preventing cognitive decline, as well as shedding light on new biological mechanisms of neuroprotection.